2022
DOI: 10.1007/s43032-022-01009-7
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital Distance and Endometriosis: Results of a Case–Control Study

Abstract: AGD is the distance measured from the anus to the genital tubercle. Recent evidence suggests that a shorter AGD, a sensitive biomarker of the prenatal hormonal environment, could be associated with higher endometriosis risk. However, studies investigating AGD in affected women are scanty. We have set up a case-control study recruiting nulliparous women (aged 18-40 years) with endometriosis between 2017 and 2018. Cases were 90 women with a surgical or with a current nonsurgical diagnosis of endometriosis (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Our results are at odds with those recently reported by Buggio et al, who found that M OE < M DE < M CT for AGD AF and M DE < M OE < M CT for AGD AC , where M denotes the mean, and OE, DE, and CT denote the patients with OE and DE and the controls, respectively, but the difference did not reach statistical significance [38]. Interestingly, for both AGD AF and AGD AC in that study, the two measurements from patients with endometriosis as a whole were 6.1% and 2.2% shorter than those of the controls, and, not surprisingly, the difference was the larger for AGD AF .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are at odds with those recently reported by Buggio et al, who found that M OE < M DE < M CT for AGD AF and M DE < M OE < M CT for AGD AC , where M denotes the mean, and OE, DE, and CT denote the patients with OE and DE and the controls, respectively, but the difference did not reach statistical significance [38]. Interestingly, for both AGD AF and AGD AC in that study, the two measurements from patients with endometriosis as a whole were 6.1% and 2.2% shorter than those of the controls, and, not surprisingly, the difference was the larger for AGD AF .…”
Section: Discussioncontrasting
confidence: 99%
“…For each woman, three AGD measurements were obtained: AGD AC , from the anterior clitoral surface (root of the clitoral hood) to the center of the anus, AGD ACt , from the tip of the clitoris to the center of the anus, and AGD AF , from the posterior fourchette to the center of the anus (Figure 1A). The measurements of AGD AC and AGD AF were identical to those in Peters et al [30] but slightly different from [17,28,29,38,54] in that we used the center of the anus instead of the upper verge of the anus in order to minimize the variation in the width of the upper verge. The tips of the digital caliper were filed to dull the sharpness.…”
Section: Measurement Of Anogenital Distancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crestani et al 18 reported, for endometriosis as a whole, a diagnostic specificity of 0.98 and a positive predictive value of 0.97, for an MRI-measured AGD-AF length of less than 20-mm. By contrast, a recent study 20 found a lack of significant difference, perhaps in part because sample sizes were relatively small. These studies are summarized in the systemic review of AGD and its relationship to endometriosis and polycystic ovarian syndrome by Pan et al 21 A shorter AGD has also been associated with several correlates of endometriosis, including low relative fertility.…”
Section: Agd As a Marker For Prenatal Testosterone Effects On Endomet...mentioning
confidence: 65%
“…As such, for the results reported here, AGD-AF can be considered as the metric that differs significantly between women with endometriosis compared to controls, with any differences in AGD-AC (in some individual studies) being attributable at least in part to its variation. These inferences are demonstrated most clearly in the results from Mendiola et al [16] and Buggio et al [21], where the distance AGD-AF is 50–100% of that for AGD-AC, such that the former accounts for the bulk of the variation in the latter.…”
Section: Discussionmentioning
confidence: 92%